2017
DOI: 10.1016/j.ypmed.2017.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Mental health predictors of breastfeeding initiation and continuation among HIV infected and uninfected women in a South African birth cohort study

Abstract: Breastfeeding is a cost-effective, yet underutilized strategy to promote maternal and infant health in low and middle income countries (LMICs). Breastfeeding remains challenging for mothers living with HIV in LMICs, yet few studies have examined mental health predictors of breastfeeding initiation and continuation. We investigated breastfeeding among mothers by HIV status in South Africa, evaluating predictors of breastfeeding initiation and continuation to identify intervention-targets. Breastfeeding patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Inconsistent with the current results, delayed initiation of breastfeeding was observed among mothers with medical disorders such as diabetes and hypertension [ 18 , 42 ]. In an African context, among maternal medical disorders, maternal human immunodeficiency virus (HIV) was found as a key barrier to early initiation of breastfeeding [ 43 45 ]. In Mauritius, despite the fact that 60.6% of mothers initiate breastfeeding, low rate of exclusive breastfeeding in the first six months were documented (17.9%) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent with the current results, delayed initiation of breastfeeding was observed among mothers with medical disorders such as diabetes and hypertension [ 18 , 42 ]. In an African context, among maternal medical disorders, maternal human immunodeficiency virus (HIV) was found as a key barrier to early initiation of breastfeeding [ 43 45 ]. In Mauritius, despite the fact that 60.6% of mothers initiate breastfeeding, low rate of exclusive breastfeeding in the first six months were documented (17.9%) [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis that evaluated the association between HIV and FI using five articles [ 9 , 13 , 14 , 17 , 28 ], PrWLWHA had a higher prevalence of FI (PR = 1.23, 95% CI 1.16–1.38) than those without HIV (Fig. 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The following information was collected from the eligible studies: author, year of publication, period, location, study design, sample, number of PrWLWHA, and diagnostic methods used for FI and FI prevalence. For clinical trials and cohort studies, the data were strained from the pregnancy baseline [9,[12][13][14][15][16][17].…”
Section: Study Selection and Data Collectionmentioning
confidence: 99%
“…Geographic biases were also clear in terms of where EBF was studied, clustering in Kwa-Zulu Natal (KZN; 17) [11, 18, 5670], the Western Cape (WC; 13) [11, 53–55, 65, 71–78], and Gauteng provinces (GP; 10) [79–88]. Five studies reported data from the Eastern Cape (EC) [11, 65, 87, 89, 90].…”
Section: Resultsmentioning
confidence: 99%